2007
DOI: 10.1002/mpr.228
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the prediction of 5‐year outcome in first episode psychosis

Abstract: This study revealed that the predictors for poor outcome differ between male and female patients with FEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…While gender has been associated with other outcome measures after FEP [34,37,38], there was no indication of influence on the late hospitalization for psychosis outcome in the current study. This illustrates the multidimensional character of outcome after FEP, and how different outcome measures may have very different dependencies on premorbid and other risk factors.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…While gender has been associated with other outcome measures after FEP [34,37,38], there was no indication of influence on the late hospitalization for psychosis outcome in the current study. This illustrates the multidimensional character of outcome after FEP, and how different outcome measures may have very different dependencies on premorbid and other risk factors.…”
Section: Discussioncontrasting
confidence: 72%
“…Demographic data for the cohort have previously been described [20,34]. 55% of the cases were males.…”
Section: Description Of the Cohortmentioning
confidence: 99%
“…They concluded that the association of cognitive deficits with sex may be found only in patients with better functional outcome. Mattsson et al (2007) showed the Global Assessment of Functioning (GAF; American Psychiatric Association, 1987) scores (current score and the highest score in the year before admission) to be valid 5-year outcome predictors for male patients but not for female patients. A low educational level was the primary predictor of the unfavorable outcome in women but not in men.…”
mentioning
confidence: 99%
“…Although, sex differences have been extensively described in first-episode psychosis (FEP), mixed results have been found in neurocognitive performance. For example, research has found that females demonstrate better premorbid adjustment (14,(23)(24)(25) and neurocognitive performance (14,23) than their male counterparts. Conversely, higher severity of negative symptoms and higher rates of substance use were more frequent in males (23).…”
Section: Introductionmentioning
confidence: 99%